RELEVANSI GAYA KEPEMIMPINAN BERBASIS ETIKA KONFUSIANISME TERHADAP PERSONNEL AND CULTURECONTROL BAGI KINERJA KARYAWAN GENERASI Y PADA UD.SETIA HATI - Felicia Felicia; Sujoko Efferin (CALYPTRA, 2018)
Leader is a very important figure of the future for a company. The existence of a company's vision and mission of a leader will affect the success of an organization. If one of the visions can not be realized, the company will experience an unwanted obstacle due to wrong consideration of a decision taken from a leader. So, the role of a leader plays a very strong role where with the support of the values of Confucian ethics are insipirational against the progress of a company. But a company needs other resources to lead to the success of employees. Human resources can consist of various generations, especially from generations X and Y which this generation has its own uniqueness in doing a job for the achievement of corporate goals. Many differences in thinking and characteristics in the company can cause potential to develop and can cause misunderstandings that cause the organization to run smoothly. Therefore, the control of management needed in controlling organizational behavior so that the company's vision and mission can be achieved. Control systems that used in UD. Setia Hati are personnel and culture control. Both are behavior controls against the individual himself and between employees so that behave in accordance with the desire of the company. This research is qualitative by taking UD Setia Hati's research object. UD. Setia Hati is a business entity providing party equipment. It is focused on knowing Confucian ethics in the leadership style that influences the personnel and culture control in order to improve the quality of employees in the company.